Herbicide Resistance Management in Florida Tomato Production - Shaun M. Sharpe; Nathan S. Boyd; Ramdas G. Kanissery; Peter J. Dittmar (EDIS, 2020)
Herbicide resistance was historically not a significant issue in most horticultural crops because few herbicides were applied. Close proximity of agronomic crops and the loss of methyl bromide has led to a gradual increase in herbicide inputs and the increased occurrence of herbicide-resistant weeds in tomato fields. Very few herbicides are registered for tomato, and resistance is a major concern. This new 11-page publication of the UF/IFAS Horticultural Sciences Department provides a definition of herbicide resistance, explains how it develops, and provides management recommendations for tomato growers. It was written for growers and Extension agents, but the information may be of interest to anyone concerned about herbicide resistance in vegetable and small fruit crops. Written by Shaun M. Sharpe, Nathan S. Boyd, Ramdas G. Kanissery, and Peter J. Dittmar. https://edis.ifas.ufl.edu/hs1398